Meat Fatty Acid and Cholesterol Content of Native Indonesian Muscovy Duck Fed with Rice Bran in Traditional Farm - Suci, Dwi Margi; Fitria, Zurrahmi; Mutia, Rita (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2017)
Fat, cholesterol and fatty acid profile of breast and thigh meat of 12 Muscovy ducks (6 drakes) aged 8 weeks from the local farm in Bogor, West Java were analyzed in thus study. In general, Muscovy ducks were fed with rice bran twice a day and free-ranged in the backyard. The nutrition of rice bran is varied in crude protein, crude fiber, fat, and ash content. Muscovy ducks were slaughtered and the percentage of carcass weight, fat, cholesterol and fatty acid profile of the breast and thigh meat were measured and analyzed. The result showed that the breast meat had higher (P<0.05) Ï3 total fatty acid EPA (C20:5Ï3) but DHA (C22:6Ï3) and linolenic acid (C18:3Ï3) were not significant compared to that of thigh meat. Concentration of linolenic acid in breast meat ranged from 0.26 to 0.51% of fat and 0.35 to 0.39% of fat in thigh meat. Linoleic acid (C18:2Ï6) in breast and thigh meat was 7.64 - 10.73% and 5.17 - 13.93 % fat, respectively. DHA concentration ranged from 0.13-1.31% fat in breast meat and EPA in thigh meat was approximately 0.08-0.32 % fat. Â EPA was significantly higher (P<0.05) in breast meat (0.03-0.28 %) than thigh meat (0.05-0.08 %) The study produced Ï 6:3 ratio ranged 6.50-24.14 and 8.94-31.64 in breast and thigh meat, respectively.